Comparison between Microscopic Identification and Nested PCR for Detection of Cutaneous Leishmaniasis at Wasit Province - Abdulsada A. Rahi; Zainab K. Hashim; Ali Mohsin Al-Jamea (Institute of Medico-legal Publications Pvt Ltd, 2021)
Cutaneous leishmaniosis in Iraq has 2 forms, zoonotic cutaneous leishmaniasis (ZCL), which is mainlycaused by Leishmania major, and anthroponotic cutaneous leishmaniasis (ACL), which is mainly causedby Leishmania tropica . Twenty skin samples were taken from suspected patients with CL and checked forLeishmania amastigote, during the period from October 2019 to February 2020 in Al-Karamah teachinghospital of Kut city, Iraq. The highest infection 100% using Giemsa- smeared and 75% using Nested PCRmethods. Totally 20 patients aged from (1- <40) years old were included in current study.The prevalenceof CL were in males 9(45) and 11(55) in females and high prevalence in age groups (>20) years old. Thecurrent study 12(60%) were brought on Leishmania major and 4(20%) Leishmania tropica using NestedPCR method . In present study the direct smear could be considered a good test for testing the cutaneousLeishmaniasis but Nested PCR assay was more touchy than parasitological technique in diagnosis ofLeishmania species in skin lesions. L.major is the main species responsible of cutaneous leishmaniasis inareas of Wasit Province.